2020
DOI: 10.1186/s13046-020-01668-x
|View full text |Cite
|
Sign up to set email alerts
|

Retraction Note: Endoplasmic reticulum stress triggers Xanthoangelol-induced protective autophagy via activation of JNK/c-Jun Axis in hepatocellular carcinoma

Abstract: An amendment to this paper has been published and can be accessed via the original article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…Human ovarian epithelial cell line IOSE‐80 and four OC cell lines A2780, SKOV3, ES‐2, and C30 were purchased from Shanghai Cell Bank of Chinese Academy of Sciences. Cells were maintained in RPMI‐1640 medium (Invitrogen, CA) supplemented with 10% fetal bovine serum (FBS) (Invitrogen, CA), and then cells were incubated in a humidified incubator at 37°C, 5% CO 2 (Li, Zhang, et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Human ovarian epithelial cell line IOSE‐80 and four OC cell lines A2780, SKOV3, ES‐2, and C30 were purchased from Shanghai Cell Bank of Chinese Academy of Sciences. Cells were maintained in RPMI‐1640 medium (Invitrogen, CA) supplemented with 10% fetal bovine serum (FBS) (Invitrogen, CA), and then cells were incubated in a humidified incubator at 37°C, 5% CO 2 (Li, Zhang, et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…JNK serine/tyrosine kinase activity is activated under pressure or stimulation by ROS, radiation, inflammatory factors, and growth factors, among other stimulators, promoting the phosphorylation of its downstream substrates (such as c-Jun, c-Fos, and ATF2), as well as the formation of the activated protein-1 (AP-1) transcription complex 22,23 . In the tumor microenvironment, cancer cells undergo proto-oncogene transformation, and the JNK signaling pathway is usually activated and plays an important role in carcinogenesis and tumor progression [24][25][26] . Via its binding to the negatively charged C-terminal region of the JNK protein, GSTP1 is a natural inhibitor of the JNK signaling pathway 14,16,27 , and GSTP1 monomers have higher JNK protein-binding activity than GSTP1 dimers.…”
Section: Discussionmentioning
confidence: 99%
“…The synergistic effect of RAD with GEM on growth inhibition of HepG2 cells depends mainly on the generation of ROS (Figure 2(a)) associated with a pronounced reduction in ATP levels (Figure 2(b)). Radiation exposure producing abundant ROS leads to formation of pores at mitochondrial membrane which causes disruption of mitochondrial membrane potential that results in impaired mitochondrial electron transport chain, decrease metabolic oxygen consumption, and ATP depletion and eventually leads to apoptosis (Li et al, 2019). Also, Donadelli et al (2007) demonstrated that the cytotoxicity of GEM-induced ROS production and increased mitochondrial membrane permeability that promotes apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the ER function is severely impaired, the organelle elicits cell death signals through activation of CHOP, which in turn is described to promote apoptosis by B-cell lymphoma gene-2 (Bcl-2)-like protein 11 (BIM) induction and Bcl-2 inhibition (Donadelli et al, 2011;Lin et al, 2019). Li et al (2019) found that excessive and prolonged ER stress could effectively abrogate the autophagy-inducing effect of CHOP and increase the apoptotic cell death. Moreover, ROS-induced JNK activation can induce apoptosis through mitochondrial membrane depolarization in breast cancer MDA-MB-231 and MCF-7 cells as well as IRE1α-mediated JNK activation is elevated in ovarian cancer SKOV3/DDP cells and induces apoptosis, and activation of JNK is associated with oxidative stress (Lin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%